ZAKAT DAN KAJIANNYA DI INDONESIA - Nurfiana, Nurfiana; Sakinah, Sakinah (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
The zakat institution is a body that manages the source of zakat funds received from the Muzakki, both individuals and business entities where the acceptance of zakat is in accordance with applicable Islamic rules or amil receiving zakat, both zakat fitrah and zakat property and zakat in other forms. This study describes zakat and examines zakat institutions in Indonesia. The literature review method is used in this study. The results of this study revealed that zakat institutions play a role in accepting zakat or distributing funds obtained from Muzakki and then given to Mustahik.